Educating Beginner Voters: Yogyakarta KPUD's Role, Criticisms, and Recommendations in 2024 Election - Akbar, M. Fabian; Lingganingrum, Laras; Mareto, Irvan; Akbar Napitupulu, Ichwan Rizki (Fakultas Hukum Universitas Lampung, 2024)
Engaging first-time voters in the 2024 General Election is vital for a healthy democracy. The General Election Commission of Yogyakarta City is concerned that many new voters lack understanding of democratic processes, which might lead to lower turnout. To address this, the Commission is running educational programs in schools and universities. This research looks at these efforts and their impact on first-time voters. It shows that effective political education can increase awareness and participation among young voters. The findings suggest that these educational programs help first-time voters get involved in the election, making the process more effective and inclusive. The research highlights the importance of ongoing political education to strengthen democratic participation.